Estudo da associação de SNPs dos genes do mecanismo de reparo por excisão de nucleotídeo em carcinoma basocelular no Estado da Paraíba - Maia, Mayara dos Santos (2017)
Basal Cell Carcinoma (BCC) is a frequent neoplasm in humans and its main etiological factor is exposure to solar radiation. Although genetic and epigenetic changes can activate proto-oncogenes, inactivate tumor suppressor genes and repair mechanism genes, the cell has several mechanisms that contribute to the maintenance of genomic stability. Mutations in repair genes can lead to tumor progression and loss of genome integrity leading to the onset of cancer. Nucleotide excision repair (NER) is an important mechanism primarily used to repair injuries caused by UV. The objective of this study was to evaluate single nucleotide polymorphisms (SNP) of XPA and XPC genes and the risk of developing BCC. One hundred samples of paraffined tissue from patients from the State of Paraíba with histopathological diagnosis of BCC were analyzed for each polymorphism. The results were obtained by a newly developed genotyping method, the Dideoxy Unique Allele Specific - PCR, a method that presents high sensitivity and low cost. Graphpad Prism 6.01 software was used for the statistical analysis and application of Chi-square and Fisher's exact test. The SNP rs535425175 of the XPC gene showed a significant association with the BCC in the analyzed samples (X2 = 14.51 and P <0.005). Whereas the SNPs rs745769173 of the XPA gene and rs761106780 of the XPC gene are in the Hardy-Weinberg equilibrium, not showing any association with the neoplasia. The results suggest that the SNP rs535425175 of the XPC gene may be considered a risk factor associated with the development of BCC.